The institutional structure of macroprudential policy in the UK: an assessment of the accountability mechanisms of the Financial Policy Committee - Kaprinis, K (2017)
This thesis examines the accountability of the macroprudential policy (MPP) authorities, concentrating on the case study of the Financial Policy Committee (FPC) of the Bank of England (BoE). It explores the appropriate design of legal safeguards through which accountability of MPP authorities in the United Kingdom can be ensured. Under its mandate, the FPC has been delegated a range of MPP instruments. These instruments are, in essence, mechanisms that control the overall level of risk-taking in the financial system and have an impact on economic growth as well as direct distributional consequences. The degree, therefore, to which MPP is used for socially beneficial purposes depends crucially on aligning the interests of this unelected authority with the interests of society for financial stability. This thesis's analysis is conducted in two steps. The first part examines the analytical framework of MPP, the legal structure of the FPC and the political economy issues stemming from the delegation of MPP to an independent authority. The second part evaluates five accountability mechanisms: (i) the transparency framework; (ii) the Non- Executive Directors of the Court of the BoE; (iii) the House of Commons Treasury Select Committee; (iv) judicial review; (v) and peer review by international MPP authorities. The main argument is that FPC members are susceptible to influence by the regulated sector which may cause the FPC to deviate from purely technocratic promotion of the public interest. Our study proposes an effective accountability regime for the FPC that should decrease the agency costs of delegation to an independent MPP authority and any subsequent welfare losses.